Determining the Types of Contrasts: The Influences of Prosody on Pragmatic Inferences - Chen, I-Hsuan; Huang, Chu-Ren; Politzer-Ahles, Stephen (Frontiers in Psychology, 2018)
This study explores the issues involving pragmatic inferences with prosodic cues. Although there is a well-established literature from multiple languages demonstrating how different pragmatic inferences can be applied to the same syntactic structure, few studies discuss whether prosody can determine types of alternative sets based on the same syntactic structure. In Mandarin Chinese, the same sentence containing a numeral-classifier phrase as a negative polarity item can be employed for two types of scalar inferences based on either the numeral or the noun. The sentence wo yi zhi mayi dou mei kan dao ("I didn't even see one ant") can induce two different scalar inferences: Quantity-contrast (‘I did not see one ant, much less two ants, three ants, and so on’ by drawing a contrast against the minimal quantity of one), and Type-contrast (‘I did not see an ant, much less a dog, a cat, a human being, and so on’ by drawing a contrast against the minimally surprising type, that of ants). Taking advantage of similar sentences with the syntactic structure and lexical items, our study examines whether prosodic conditions can guide people to choose pragmatic inferences from a set of options based on the same syntactic structure. The experiments of this study are designed to answer whether prosody interacts with contextual information in this grammatical structure. The results suggest that Mandarin speakers can use sentence prosody to determine which inference is intended, at least in experimental contexts that directly probe explicit awareness of prosody. Prosody does play a role in inducing scalar inferences, but contextual information can override the effects of prosody. Each prosodic pattern can evoke a specific set of scalar inferences, but quantity-contrast inferences are favored over type-contrast inferences. Our experiments show that prosodic prominence can serve as a linguistic cue to pragmatic inferences.